Ramadan and match physical performance in professional Muslim football players: a three‐phase interrupted time-series league-wide study from the Qatar Stars League - Valter Di Salvo (3094752) (2025)
To explore the effects of Ramadan on proxy measures of match physical performance in professional Muslim football players competing in the Qatar Stars League using a three-phase interrupted time-series design. We examined total, high-speed running ( > 15 km·h−1), very-high speed running ( > 20 km·h−1), and sprinting ( > 25 km·h−1) distances covered (m) by 45 professional Muslim football players tracked during official matches (322 individual measurements over 10 consecutive league rounds) and training (1168 individual observations) in periods preceding, during, and after Ramadan 1445. Separate multivariable-adjusted random-effects generalized additive models quantified the phase-specific effects of Ramadan on match running distances interpreted against the random match-to-match variability in total, high-speed running, very-high speed running, and sprinting distance of ± 494 m (95% confidence interval [CI], 480 to 508 m), ±200 m (95% CI, 195 to 206 m), ±102 m (95% CI, 99 to 105 m), and ± 60 m (95% CI, 58 to 61 m), respectively. Model-based phase-specific effects of Ramadan indicated mean reductions of 254 m (95% CI, 138 to 370 m) in total distance, 92 m (95%CI, 59 to 123 m) in high-speed running, and 31 m (95% CI, 12 to 50 m) in very high-speed running distance that were indistinguishable from random within-subject match-to-match variability. Effects for sprinting distance were inconsistent. Running distances covered during training were materially equivalent across study phases. In Muslim-majority environments like the State of Qatar, professional Muslim football players seem able to cope with Ramadan without experiencing substantial impairments in match physical performance or reductions in training load. Other Information Published in: Science and Medicine in Football License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/24733938.2025.2550414